Big Constraints or Small Returns? Explaining Nonadoption of Hybrid Maize in Tanzania - Jonas Kathage; Matin Qaim; Menale Kassie; Bekele A. Shiferaw (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
Modern technologies are often not widely adopted among smallholder farmers in Sub-Saharan Africa. Several adoption constraints have been discussed in the literature, including limited access to information. Using survey data from farmers in Tanzania and the average treatment effect framework, we question the hypothesis that limited information is an important constraint for the adoption of hybrid maize technology. While we find an adoption gap from incomplete awareness exposure, this gap is sizeable only in the east of Tanzania, where productivity effects of hybrids are small. In the north, where adoption is much more beneficial, almost all farmers are already aware of hybrids. The results suggest that exposure to a new technology may be a function of expected returns to adoption. We also test for other constraints related to credit and risk, which do not determine adoption significantly. More generally, nonadoption of technologies is not always a sign of constraints but may also indicate low benefits. Some policy implications are discussed.
Keywords: O13; O33; Q12; Q16; 330; farm survey; technology adoption; hybrid maize; Tanzania